Introduction and Consultation on the Indonesia's Oil and Gas Sharing Contract at CNG Co. - Prayang Sunny Yulia; R. Hari Karyadi Oetomo; Arinda Ristawati; Aqlyna Fattahanisa; Riskaviana Kurniawati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Indonesia's oil and gas sector has traditionally employed Production Sharing Contracts (PSCs) to regulate the sharing of revenues between the government and contractors. Two key PSC models are used: PSC Cost Recovery and PSC Gross Split. The PSC Cost Recovery model allows contractors to recover their exploration and production costs before profits are shared, providing financial protection but reducing long-term profitability. Conversely, the PSC Gross Split model, introduced in 2017, offers a simpler revenue-sharing mechanism, eliminating cost recovery and directly splitting gross revenue between the government and contractors. This study analyzes the financial implications of both models using economic simulations, focusing on key indicators like net cash flow, net present value (NPV), pay-out time, and discounted cash flow (DCF) rate of return. Results show that the Gross Split model generates significantly higher gross revenue (420.908 million) than Cost Recovery (46.362 million), but at the cost of greater financial risks for contractors due to higher upfront investments and operating costs. The Gross Split model also provides higher long-term returns, with a net cash flow of 67.138 million compared to 8.252 million in Cost Recovery. However, the pay-out time is longer, and the DCF rate of return is slightly lower (29.95% vs. 31.8%). Ultimately, PSC Gross Split is more suited for contractors with higher risk tolerance and capital resources, while PSC Cost Recovery may be preferable for smaller contractors seeking to minimize financial risks. Both models offer distinct advantages depending on the contractor’s financial capacity and risk appetite.